ANALISIS KONSEPTUAL PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN, DAN MOTIVASI TERHADAP KEPUTUSAN JAMAAH DALAM MEMILIH LAYANAN HAJI DAN UMROH DI EL-HAKIM UMRAH HAJJ SERVICES: STUDI LIBRARY RESEARCH - Achmad Rofi’i; Jauharotina Alfadhilah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to conceptually analyze the influence of service quality, trust, and motivation on the congregation's decision to choose hajj and umrah services at El-Hakim Umrah Hajj Services. The background of the research is based on the increasing competition among service providers and the uncertainty that affects the congregation's trust. The method used is qualitative research with a library research approach, where data were obtained from scientific journals, books, and relevant academic sources, then analyzed descriptively and comparatively. The results show that service quality, which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, plays an important role in shaping the congregation's perception. Good service quality is proven to increase trust, which subsequently serves as a mediating variable in influencing the congregation's decision. Furthermore, religious motivation becomes the dominant factor driving the congregation to choose services while also strengthening the relationship between trust and decision. The integration of these three variables results in a conceptual model showing that the congregation's decision is an outcome of the interaction between external (service quality), relational (trust), and internal (motivation) factors. This study provides a theoretical contribution in the form of a conceptual model that integrates service quality, trust, and motivation in the context of religious-based services. Practically, the findings can serve as a reference for hajj and umrah service providers in designing more effective, transparent, and congregation-oriented service strategies.